The Effects of Temperature and Growth Phase on the Lipidomes of Sulfolobus islandicus and Sulfolobus tokodaii - Jensen, Sara Munk (Life (Basel), 2015)
The functionality of the plasma membrane is essential for all organisms. Adaption to high growth temperatures imposes challenges and Bacteria, Eukarya, and Archaea have developed several mechanisms to cope with these. Hyperthermophilic archaea have earlier been shown to synthesize tetraether membrane lipids with an increased number of cyclopentane moieties at higher growth temperatures. Here we used shotgun lipidomics to study this effect as well as the influence of growth phase on the lipidomes of Sulfolobus islandicus and Sulfolobus tokodaii for the first time. Both species were cultivated at three different temperatures, with samples withdrawn during lag, exponential, and stationary phases. Three abundant tetraether lipid classes and one diether lipid class were monitored. Beside the expected increase in the number of cyclopentane moieties with higher temperature in both archaea, we observed previously unreported changes in the average cyclization of the membrane lipids throughout growth. The average number of cyclopentane moieties showed a significant dip in exponential phase, an observation that might help to resolve the currently debated biosynthesis pathway of tetraether lipids.